COLLABORATIVE DIFFERENTIATED LEARNING AND AWARENESS OF STUDENTS' WELL-BEING - Triyo Supriyatno; Zaharah binti Hussin; Muhammad Ibrahim; Titien Koesoemawati; Cyril Musaddad Abbud El Aribi (RADJA PUBLIKA, 2025)
This study explores the application of collaborative differentiated learning to improve students' well-being by involving parents and the community during the Covid-19 pandemic. Conducted at MTsN Malang City, this descriptive qualitative research gathered data through in-depth interviews, participant observations, and documentation. The findings reveal that collaborative differentiated learning fosters a positive and joyful atmosphere in online learning environments. Students demonstrated increased enthusiasm, independence, and active participation. Teachers became more aware of the importance of designing learning activities based on the varied learning styles of students. Parental involvement and support from community members also enhanced students' learning experiences and emotional well-being. This study highlights the significance of differentiated and collaborative learning approaches in nurturing holistic student development, particularly in challenging learning conditions.